Soil-based systemic delivery and phyllosphere in vivo propagation of bacteriophages: Two possible strategies for improving bacteriophage persistence for plant disease control - Iriarte, Fanny B.; Obradović, Aleksa; Wernsing, Mine H.; Jackson, Lee E.; Balogh, Botond; Hong, Jason A.; Momol, M. Timur; Jones, Jeffrey B.; Vallad, Gary E. (My University, 2012)
Soil-based root applications and attenuated bacterial strains were evaluated as means to enhance bacteriophage persistence on plants for bacterial disease control. In addition, the systemic nature of phage applied to tomato roots was also evaluated. Several experiments were conducted applying either single phages or phage mixtures specific for Ralstonia solanacearum, Xanthomonas perforans or X. euvesicatoria to soil surrounding tomato plants and measuring the persistence and translocation of the phages over time. In general, all phages persisted in the roots of treated plants and were detected in stems and leaves; although phage level varied and persistence in stems and leaves was at a much lower level compared with persistence in roots. Bacterial wilt control was typically best if the phage or phage mixtures were applied to the soil surrounding tomatoes at the time of inoculation, less effective if applied 3 days before inoculation, and ineffective if applied 3 days after inoculation. The use of an attenuated X. perforans strain was also evaluated to improve the persistence of phage populations on tomato leaf surfaces. In greenhouse and field experiments, foliar applications of an attenuated mutant X. perforans 91-118:ΔOPGH strain prior to phage applications significantly improved phage persistence on tomato foliage compared with untreated tomato foliage. Both the soil-based bacteriophage delivery and the use of attenuated bacterial strains improved bacteriophage persistence on respective root and foliar tissues, with evidence of translocation with soil-based bacteriophage applications. Both strategies could lead to improved control of bacterial pathogens on plants.
Citation: Iriarte, F., Obradovic, A., Wernsing, M., . . . Vallad, G. (2012). Soil-based systemic delivery and phyllosphere in vivo propagation of bacteriophages. Bacterioophage, 2(4), 215-224. https://doi.org/10.4161/bact.23530
Keywords: Bacteriophage; Biocontrol; Phage; Tomato